Adopting Sustainable Behavior in Institutions of Higher Education: A Study on Intentions of Decision Makers in the MENA Region - Almarshad, Sultan O. (European Journal of Sustainable Development, 2017)
The aim of this study is to integrate the Protection Motivation and Habit theories to highlight and supplement the shortcomings of previous research. A systematic random sampling technique was employed to generate a sample of 1537 universities and colleges of MENA; a web questionnaire was emailed to the institutions, different analytical methods were used to analyse the data. The results show that (1) Protection Motivation Theory is valuable to apply specifically since it introduces the concept of coping appraisal, and (2) that Habit Theory is a suitable framework that can be employed to shed further insight on sustainable behaviour in higher education institutions. The findings both strengthen and expand previous knowledge on sustainable behaviour in higher education. Contrary to our expectations, habit does not moderate the relationship between all the dimensions of the cognitive process and the intention to adopt sustainability by decision makers. Keywords Sustainability, Protection Motivation Theory, Habit Theory, Higher Education, Decision makers.